Play in juvenile greater rheas: different modes and their evolutionary and socio-cognitive implications. Issue 1 (2nd January 2023) - Zeiträg, Claudia; Jensen, Thomas Rejsenhus; Osvath, Mathias
ABSTRACT: Even if there is evidence of play from all vertebrate classes suggesting origins in deep time, descriptions of the evolution of play are surprisingly patchy. To bridge this gap, one must study play comparatively and include taxa from key phylogenetic positions. This study is the first systematic description of play in greater rheas, and thereby the first such report on any palaeognath bird. Palaeognaths represent a major subgroup of modern-day birds that have retained many ancestral features from their direct ancestors, the non-avian dinosaurs, making them an ideal window into the behaviors of the earliest birds. We recorded play behaviors of a group of captive rheas, with a focus on the modes and ontogenetic development of their play. Juveniles predominantly engaged in contagious locomotor play, adding a social component to the majority of their play bouts. Interactive social play such as wrestling appeared only around the age of 10.5 weeks and was generally rarer. Based on our findings we hypothesize that early birds, and likely also paravian dinosaurs, played in a similar fashion with a noticeable component of sociality. These hypotheses need to be expanded through more studies on different species of palaeognath birds.